An Interpretation of Nurse-Patient Relationships in Inpatient Psychiatry - Catherine Thibeault (SAGE Publishing, 2016)
Nurses who work in acute inpatient psychiatry, where lengths of stay are increasingly shortened, struggle to establish therapeutic nurse-patient relationships. The purpose of this inquiry was to illuminate the nature of relationships between inpatient psychiatric mental health (PMH) nurses and their patients. The author used semistructured interviews and nonparticipant observation in an interpretive phenomenological inquiry. The data consisted of texts that were transcribed from narratives and observations. The meanings that were generated led to the uncovering of patterns of commonality, or themes. Of the themes uncovered, the theme of mindful approach highlighted PMH nurses as engaging with patients in distress, strategically creating encounters to establish a basis for ongoing therapeutic work. The PMH nurse-patient relationship in acute inpatient psychiatry continues to be under pressure, but nurses still carefully construct relational approaches in response to patient distress, and patients in these settings experience these approaches as meaningful to their recovery.